Post-Transplant Fecal Carriage of Antibiotic Resistant and ?-Lactamases-Producing Enterobacteriales among Renal Transplant Recipients - Joshi, Bindira; Yadav, Santosh Kumar; Shakya Hada, Manju Shree; Shrestha, Sabina; Shrestha, Kalpana Kumari; Shrestha, Pukar Chandra; Awal, Bal Krishna (Journal of Nepal Health Research Council, 2024)
Background: The intestinal colonization and transmission of antibiotic-resistant Enterobacteriales to renal transplant recipients may pose a threat to them because they are profoundly immunocompromised and vulnerable to infection. Hence, it is crucial to identify these antibiotic-resistant fecal Enterobacteriales harboring high-risk populations. The objective of this study was to determine antibiotic resistance as well as ?-lactamases production in fecal Enterobacteriales among renal transplant recipients.Methods: The stool samples, one collected from each transplant recipient, were processed for isolation and identification of Enterobacteriales and were tested for their antibiotic susceptibility, extended-spectrum ?-lactamase, and metallo-?-lactamase production by standard methods.Results: A total of 103 Enterobacteriales comprising of Escherichia coli (86.4%), Klebsiella species (11.7%), and Citrobacter species (1.9%) were isolated and more than 60% of the E. coli were found resistant to ceftazidime and ciprofloxacin and around half of the Klebsiella species were resistant to ceftazidime and fluroquinolones. The extended-spectrum ?-lactamase production was seen in 3.4% and 8.3% and metallo-?-lactamase production in 24.7% and 33.3% of E. coli and Klebsiella species, respectively. The high proportion of ?-lactamase-producers were resistant to piperacillin-tazobactam, meropenem, gentamicin, and amikacin than ?-lactamases non-producers.Conclusion: Since the antibiotic resistance is higher in fecal Enterobacteriales, each renal transplant recipient should be screened for these highly resistant intestinal colonizers after transplantation in order to prevent infections and to reduce the rate of transplant failure due to infections.Keywords: Antibiotic resistance; ?-lactamases; enterobacteriales; fecal carriage; renal transplantation.